Short-Term, Equipment-Free High Intensity Interval Training Elicits Significant Improvements in Cardiorespiratory Fitness Irrespective of Supervision in Early Adulthood - Tanvir S. Sian; Tanvir S. Sian; Thomas Inns; Amanda Gates; Brett Doleman; Nima Gharahdaghi; Philip J. Atherton; Jon N. Lund; Jon N. Lund; Bethan E. Phillips (Frontiers Media S.A., 2021)
Introduction: Serious health implications from having low levels of cardiorespiratory fitness (CRF) and being overweight in young adulthood are carried forward into later life. High-intensity interval training (HIIT) is a time-effective, potent stimulus for improving CRF and indices of cardiometabolic health. To date, few studies have investigated the use of equipment-free HIIT or the impact of supervision for improving CRF via HIIT.Methods: Thirty healthy young adults (18-30 y) were randomised to 4 weeks (12 sessions) equipment-free, bodyweight based supervised laboratory HIIT (L-HIIT), unsupervised home HIIT (H-HIIT) or no-intervention (CON). Utilised exercises were star jumps, squats and standing sprints. Measurements of CRF (anaerobic threshold (AT) and VO2peak), blood pressure (BP), body mass index (BMI), blood glucose and plasma insulin by oral glucose tolerance test (OGTT), and muscle architecture were performed at baseline and after the intervention.Results: When compared to the control group, both HIIT protocols improved CRF (AT: L-HIIT mean difference compared to the control group (MD) +2.1 (95% CI: 0.34-4.03) ml/kg/min; p = 0.02; H-HIIT MD +3.01 (1.17-4.85) ml/kg/min; p = 0.002), VO2peak: L-HIIT (MD +2.94 (0.64-5.25) ml/kg/min; p = 0.01; H-HIIT MD +2.55 (0.34-4.76) ml/kg/min; p = 0.03), BMI (L-HIIT MD −0.43 (−0.86 to 0.00) kg/m2; p = 0.05; H-HIIT: MD −0.51 (−0.95 to −0.07) kg/m2; p = 0.03) and m. vastus lateralis pennation angle (L-HIIT MD 0.2 (0.13-0.27)°; p < 0.001; H-HIIT MD 0.17 (0.09 to 0.24)°; p < 0.001). There was no significant change in BP, blood glucose or plasma insulin in any of the groups.Conclusions: Four weeks time-efficient, equipment-free, bodyweight-based HIIT is able to elicit improvements in CRF irrespective of supervision status. Unsupervised HIIT may be a useful tool for counteracting the rise of sedentary behaviours and consequent cardiometabolic disorders in young adults.